INTERVENSI KEGAWATDARURATAN PSIKIATRI PADA SKIZOFRENIA: SYSTEMATIC LITERATURE REVIEW - Pragholapati, Andria; Fitrikasari, Alifiati; Handayani, Fitria (Yayasan Healing and Healthcare Education, 2025)
Schizophrenia is a serious mental disorder that affects around 1% of the world's population. Some patients with schizophrenia experience psychiatric emergencies that require prompt and appropriate intervention to reduce the risk of complications and promote a good outcome. This systematic literature review aims to describe of emergency psychiatric interventions in schizophrenia. The results of the review show that appropriate and prompt intervention are very important in reducing the risk of complications and improving good outcomes in schizophrenic patients who experience psychiatric emergencies. Some effective interventions include administering antipsychotic drugs, inhaled loxapine and providing non-pharmacological interventions, namely verbal de-escalation. However, more research is needed to clarify the benefits and effectiveness of each of these interventions. Suggestions that can be given are increasing public awareness about the symptoms of schizophrenia and what to do in an emergency situation, special training for medical personnel and emergency workers, as well as further research on emergency psychiatric interventions in schizophrenia.